2009
DOI: 10.2355/isijinternational.49.827
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Model and Reduction Behavior of Carbon Iron Ore Composite in Blast Furnace

Abstract: Decreasing the carbon dioxide emission from steel industries is an important issue. It is considered that due to the high reactivity of carbon iron ore composite, it can control the thermal reserve zone temperature and decrease the consumption of reducing agents in blast furnace. In the present study, a reaction model of the carbon iron ore composite based on a lumped system is proposed to analyze the reduction behavior in the blast furnace. This model is composed of several reaction steps between carbon, iron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 8 publications
1
44
0
Order By: Relevance
“…The apparatus is same to previous study, 10) therefore, that is briefly mentioned here. An electric resistance furnace connected to a proportional-integral-derivative (PID) controller with a thermocouple was used for the measurement.…”
Section: Experimental Apparatusmentioning
confidence: 99%
“…The apparatus is same to previous study, 10) therefore, that is briefly mentioned here. An electric resistance furnace connected to a proportional-integral-derivative (PID) controller with a thermocouple was used for the measurement.…”
Section: Experimental Apparatusmentioning
confidence: 99%
“…This close contact between the reactants generally has the effect of increasing the reduction rate [1][2][3][4][5][6] . Iron ore-carbon compacts are being utilised in new ironmaking processes such as FASTMET, ITmk3 or HiQIP 7 .…”
Section: Introductionmentioning
confidence: 99%
“…The use of iron ore-carbon compacts allows the use of different iron sources such as iron ore fines, low grade iron ores 6 , plant waste 3,8 or magnetite ores 9 . The use of different carbon sources such as coal, coke 4 , biomass 10,11 and plastic waste [12][13][14] have also been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Reduction of iron oxides by solid reductants has also been studied, especially when developing the self reducing iron oxide and carbon composite briquettes. [20][21][22][23][24][25][26][27][28] These studies, with different iron oxides and carbon bearing materials, have shown that the self reduction mechanism and kinetics are more complicated because beside the reaction of reduction it includes sensibly endothermic carbon gasification reaction which very often is found to control the overall rate of self reduction. Moreover, other phenomena could influence 28) (like a devolatilization of the reducing agent) or even control 24) (like a heat transfer) the rate of self reduction.…”
Section: Introductionmentioning
confidence: 99%